Effects of different delivering matrices of β-glucan on lipids in mildly hypercholesterolaemic individuals: a meta-analysis of randomised controlled trials. Issue 3 (14th February 2021) - Xu, Dengfeng; Liu, Hechun; Yang, Chao; Xia, Hui; Pan, Da; Yang, Xian; Yang, Ligang; Wang, Shaokang; Sun, Guiju
Abstract: β-Glucan has been reported for its health benefits on blood lipids in hypercholesterolaemic individuals for years. However, people have paid little attention to the effects of β-glucan in populations with mild hypercholesterolaemia as well as the various delivering matrices. Our objective was to perform a meta-analysis to analyse the effects of β-glucan with different delivering matrices in mildly hypercholesterolaemic individuals. After conducting a comprehensive search in Web of Science, PubMed, Scopus and Cochrane Library, a total of twenty-one randomised controlled trials involving 1120 participants were identified to measure the pooled effect. The overall results indicated that consuming a dose of ≥3 g/d of β-glucan for at least 3 weeks could significantly reduce total cholesterol (TC) (−0·27 mmol/l, 95 % CI −0·33, −0·21, P < 0·001) and LDL-cholesterol (−0·26 mmol/l, 95% CI −0·32, −0·20, P < 0·001) compared with the control group in mildly hypercholesterolaemic individuals, while no significant difference was observed in TAG (−0·03 mmol/l, 95% CI −0·11, 0·06, P = 0·521) and HDL-cholesterol (0·01 mmol/l, 95% CI −0·03, 0·04, P = 0·777). There was evidence for modest unexplained heterogeneity in the meta-analysis. In conclusion, β-glucan can significantly reduce risk factors like TC and LDL-cholesterol for CVD in mildly hypercholesterolaemic individuals; furthermore, it appears that the effects of food matrices with both 'solid products' and 'liquid products' where β-glucan was incorporated into were ranked as the best way to exert its beneficial properties, while 'liquid' and 'solid' products were ranked as the second and third positions, respectively.